PENINGKATAN MINAT DAN HASIL BELAJAR MEMPROSES BUKU BESAR MELALUI PEMBELAJARAN TUTOR SEBAYA PADA KELAS X AKUNTANSI 3 SMK N I SALATIGA SEMESTER GENAP TAHUN 2013/2014 - Wardani, Utami Kusuma (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
The formula of this research is how the peer teaching can improve the students interest and result in processing general leger. This study was class action research which was designed into two main cycles ,The model of his reserch is 10 accounting 3 class of SMK N 1 Salatiga periode 2013/2014. The result showed that:1) The interest in learning increase 41,53 % from 37,11 before cycle, 61,83% in first cycle and 78,7% in second cycle, ;2) The learning outcomes increase 67,11% from 30,55% before cycle, 63,88% in first cycle and 91,66% in second cycle.